Pelelangan Proyek Konstruksi Berbasis Internet - Maksum Tanubrata; Hendaryanto Wiryopranoto (Universitas Kristen Maranatha, 2015)
Procurement implementation by auction can be done efficient, effective and comparable,transparent, fairness, not discriminative and accountable with the system which can accommodatethe above criteria.With the fast development of information technology the above implementationcan be realized with the online auction system base on internet by web. E-procurement, it is anapplication for auction implementation by electronic with internet basis where web as animplementation medium. This application can be used as an announcement, document storagealso as a tool in selection process. With internet base the interaction between buyers and vendorscan be optimized without any limitation in distance and time.